Understanding cryptic crosswords: a step by step guide - Singh, Vivek Kumar (Patna Mahia, 2020)
This book is meant to be used as a primer, a workbook and a reference book, all rolled into one. It unlocks the secrets of cracking a cryptic crossword in simple steps, and presents a collection of crosswords to practice and enjoy.
Keywords: Crossword puzzles